Protecting Widows and Disableds. State Interventions on The Guerreros Del Paraguay and Their Bereaved Relatives During the Long Post-War Period of The Triple Alliance in Argentina (1865-1915) - Chao, Luis Daniel (Revista de Historia Social y de las Mentalidades, 2023)
We address a series of state interventions around the figure of the Triple Alliance’s veterans (guerreros del Paraguay). In the first part of this study, we analyze the long duration of war pensions from the nineteenth century to the first decade of the twentieth century, which included widows and survivors of the english invasions, the wars of Independence and Brazil, in order to reflect on the singularity of those that attended to the Triple Alliance’s veterans. In the second, we focus on the specific measures aimed at widows and survivors of the War of the Triple Alliance in the period 1865-1915; while in the third, we focus on the case of war invalids, specifically on the actions of the Asociación Protectora de Inválidos during 1867-1868. We seek to understand the characteristics of the warrior as a state problem and social question during the second half of the 19th century
Keywords: Triple Alliance; Veterans; State; Social Question